2010
DOI: 10.1590/s1516-35982010001300038
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in small ruminants' health and production

Abstract: This paper examines the role that oxidative stress plays in small ruminant medicine. We will examine how redox homeostasis is involved in some physiological functions and we will discuss the implications of the impairment of oxidative status on small ruminant health and production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
122
1
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 156 publications
(194 reference statements)
10
122
1
20
Order By: Relevance
“…Dietary supplementation with vitamin E or vitamin D3 can increase the levels of GSH in the liver (Sardar et al 1996). MDA, the main representative of the thiobarbituric acid-reactive substances that arises during the peroxidation of fatty acids by ROS, is considered to be a marker of cellular damage and oxidative stress because its concentration increases with excess ROS (Celi 2010). In the present study, the lowest post-weaning levels of GSH were found in the treated group.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Dietary supplementation with vitamin E or vitamin D3 can increase the levels of GSH in the liver (Sardar et al 1996). MDA, the main representative of the thiobarbituric acid-reactive substances that arises during the peroxidation of fatty acids by ROS, is considered to be a marker of cellular damage and oxidative stress because its concentration increases with excess ROS (Celi 2010). In the present study, the lowest post-weaning levels of GSH were found in the treated group.…”
Section: Discussionsupporting
confidence: 46%
“…SOD, an endogenous antioxidant, belongs to the class of metalloenzymes that counteract superoxide anion toxicity (Celi 2010). SOD is the most abundant enzymes and is the ϐifth most abundant protein in quantitative terms.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increase on oxidative stress in plasma during the follicular phase of the estrous cycle may be closely related to the oxygen demand as a result of cell growth and synthesis activity [20] . In addition, lipids, especially due to compositional properties of LDL-C, are one of the most susceptible substrates to lipid peroxidation [22] . Because of LDL-C susceptibility to oxidation, its high level may be a reason of increased oxidative stress at the follicular phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of PGF2α on progesterone production by the CL is due in part to increased ROS. In addition, progesterone levels decrease due to the destructive effects of oxidative stressors on luteal cell steroidogenesis [116][117][118]. ROS can also inhibit progesterone synthesis through inhibition of cytochrome P450, mitochondrial intracellular transport of cholesterol, and degradation of LH receptors [112].…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%
“…In sheep, the regulation of reproductive physiology is related to the effects of oxidative stress [117]. Increased levels of progesterone during pregnancy in sheep and goats as well as increased levels of malondialdehyde (MDA) in placentomas have been reported [131].…”
Section: Relationship Between Progesterone and Oxidative Stress In Rumentioning
confidence: 99%